Das Johannesevangelium und die antike griechische Philosophie Untersuchung des philosophischen Hintergrunds der langen Reden Jesu im JohEv Band 1 (Joh 1-12) - Despotis, Athanasios 1979- (Leiden Boston Brill, 2025)
"This monograph offers a detailed commentary on Jesus's long speeches in John 1-12, revealing how the Gospel of John engages with the religious and philosophical discourses of its time. By examining these speeches, the study uncovers how John creates new syntheses, integrating sophisticated grammatical and rhetorical features. It also explores the ancient patristic exegesis, ensuring a nuanced understanding of the historical and cultural context of the New Testament. This work provides fresh insights into the intersection of philosophy, rhetoric, and theology in the Johannine corpus"
Literaturverzeichnis Seite 275-307
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Bible -- Commentaries; Rhetoric in the Bible; Philosophy, Ancient